Do e-service quality and e-recovery service quality affect e-satisfaction? A study on mobile banking users - Annita Maharani Kamil; Dian Fordian (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — This study aims to analyze the roles of e-service quality and e-recovery service quality on e-satisfaction in the mobile banking app.Method — The research method was conducted quantitatively using a descriptive-analytic method and verification analysis. A survey was conducted using a questionnaire instrument with 400 samples of active Indonesian mobile banking users. The collected data were analyzed using multiple regression analysis.Result — This study found that e-service quality and e-recovery service played a significant role in influencing the e-satisfaction of the users, both simultaneously and partially. The role of these two competencies is positive, indicating the progressive impact of e-service quality and e-recovery service quality on the users' e-satisfaction.Contribution — This research makes a significant academic contribution by providing valuable insights into the intricacies of e-service quality and e-recovery service quality concepts and their coherence with customer satisfaction in the context of marketing services, while also offering relevant and updated insights into the mobile banking subsector within the digital business landscape.